Analysis of the Teacher's Role in Arranging the Study Room at Al-Kindi Middle School, Depok - Adrian Ariel Pamungkas; Siskha Putri Sayekti; Rifa A-intishar; Shafa Khalisha Hasan; Deni Al-Malikussholeh (Mazidah: Journal Of Educational Research, 2025)
Effective learning starts from a good classroom arrangement. This research aims to analyze the role of teachers in organizing learning spaces at Al-Kindi Cipayung Middle School, Depok. The research was taken in class VIII-2 which consisted of 22 students. The research method used is a case study type qualitative research method to describe the way the teacher organizes the classroom space and climate during learning. Data was collected by observation, interviews and documentation. The research results show that the arrangements for class VIII-2 have not run optimally. The classroom setting has an important influence on the effectiveness of the resulting learning climate in the classroom setting. Teachers, homeroom teachers and student guardians, together with class administrators, can pay more attention to class management and organization.